HIJAB IN THE QUR’AN (Comparative Study of Tafsir Al-Mishbah and Tafsir Al-Azhar) - Faridatus Ovi Shofiyah (Sekolah Tinggi Agama Islam Almuhammad Cepu, 2021)
The hijab, which is special clothing for Muslim women, has become a trend in Indonesia in recent years. But over time, emerging models of the hijab that seem rulled out the function of the veil itself, so that the use of the hijab seems not accordance from its original function. On the other hand, there are still many Indonesian women who have not worn this Muslim dress with several pretexts. In this research, the author compares with the opinion of two Indonesian commentators, namely Prof. Dr. M. Quraish Shihab and Dr. Abdul Malik Karim Amrullah, they both have different points of view regarding the hijab. Furthermore, the research question is; what is the the hijab in the Qur’an, and how the views of Quraish Shihab and Hamka relate to the verse of the hijab.To make this research systematic, the researcher uses the descriptive-comparative method by comparing the thoughts of Quraish Shihab and Hamka regarding the hijab through their two works of interpretation, namely the tafsir al-Misbah and tafir al-Azhar, as well as other references that are still related to the theme. Furthermore, from the author's analysis, it can be concluded that the hijab in the Qur'an is a woman's honorable clothing, which in defining it the scholars still have different opinions. Meanwhile, Hamka and Quraish Shihab view that the command to veil (use jilbab) in the Qur'an is actually an order to wear respectable and polite clothes, while the model it is various according to the traditions and culture of each region, because the Qur'an does not specifically mention it, details about the dress model. However, in his tafsir Quraish Shihab also included a different opinion from the majority of scholars by quoting the words of Ibn Asyur, who said the hijab as the culture of the Arabs, but here Quraish Shihab did not step on the attitude of tarjih, only expressed the diversity of opinions of experts without setting one options.